Leadership Essentials You Always Wanted to Know - Vibrant Publishers (Broomfield, Colorado); Picardi, Carrie (2021)
"Leadership Essentials guides readers through the trends, challenges, and areas of focus for leaders across all areas of society and provides tools and resources for effective leadership in a diverse array of contexts and settings. It provides an understanding of areas including: The meaning and purpose of leadership Different types of leader roles The leader-follower relationship. Leadership attributes and traits. Effective leadership behaviors and competencies Power and influence. Charismatic and transformational leadership. Situational and contingency leadership. Leading teams. Decision making. Conflict resolution. Ethical leadership. Leadership development and coaching. Global leadership. Organizational development. Leading change"--